Trichomonas vaginalis Infection and Associated Risk Factors in a Socially-Marginalized Female Population in Coastal Peru. (29th June 2009) - Leon, Segundo R.; Konda, Kelika A.; Bernstein, Kyle T.; Pajuelo, Jose B.; Rosasco, Ana M.; Caceres, Carlos F.; Coates, Thomas J.; Klausner, Jeffrey D.
Abstract : Objective. The epidemiology of Trichomonas vaginalis infection among sexually active socially-marginalized women in three urban, coastal Peruvian cities was examined in order to quantify the prevalence of trichomonas infection and identify associated risk factors. Methods . We conducted a cross-sectional, venue-based study of women from socially-marginalized populations in three coastal Peruvian cities. Results . Among the 319 women enrolled, the overall prevalence of trichomonal infection was 9.1% (95% CI, 5.9%–12.3%). The mean age was 26.3 years, and 35.5% reported having had unprotected intercourse with nonprimary partners and 19.8% reported two or more sex partners in the last three months. Trichomonal infection was associated with increased number of sex partners (PR 2.5, 95% CI 1.4–4.6) and unprotected sex with nonprimary partner in the last three months (PR 2.3, 95% CI 1.1–4.9). Conclusions . A moderately high prevalence of trichomonal infection was found among women in our study. Trichomonal infection was associated with unprotected sex and multiple sex partners. Efforts to control the continued spread of trichomonal infection are warranted.